Protective Effects of Sodium-Glucose Transporter 2 Inhibitors on Atrial Fibrillation and Atrial Flutter: A Systematic Review and Meta- Analysis of Randomized Placebo-Controlled Trials - Li, Daobo; Liu, Yingying; Hidru, Tesfaldet Habtemariam; Yang, Xiaolei; Wang, Yunsong; Chen, Cheng; Li, Ka Hou Christien; Tang, Yuqi; Wei, Yushan; Tse, Gary; Xia, Yunlong (Frontiers in Endocrinology, 2021)
Background: Hyperglycemia is associated with an increased risk of developing atrial fibrillation (AF) and atrial flutter (AFL). Sodium-glucose transporter 2 inhibitors (SGLT2i) have been reported to prevent AF/AFL in some studies, but not others. Therefore, a meta-analysis was performed to investigate whether SGLT2i use is associated with lower risks of AF/AFL. Methods: PubMed, Scopus, Web of Science, Cochrane library databases were searched for randomized placebo-controlled trials comparing SGLT2i and placebo. Results: A total of 33 trials involving 66,685 patients were included. The serious adverse events (SAEs) of AF/AFL occurrence were significantly lower in the SGLT2i group than the placebo group (0.96% vs. 1.19%; RR 0.83; 95% CI 0.71-0.96; P=0.01; I2 25.5%). Similarly, the SAEs of AF occurrence was significantly lower in the SGLT2i group (0.82% vs. 1.06%; RR 0.81; 95% CI 0.69-0.95; P=0.01; I2 10.2%). The subgroup analysis showed that the reduction in AF/AFL was significant only for dapagliflozin (1.02% vs. 1.49%; RR 0.73; 95% CI 0.59-0.89; P=0.002; I2 0%), but not for canagliflozin (1.00% vs 1.08%; RR 0.83; 95% CI 0.62-1.12; P=0.23; I2 0%), empagliflozin (0.88% vs 0.70%; RR 1.20; 95% CI 0.76-1.90; P=0.43; I2 0%), ertugliflozin (1.01% vs 0.96%; RR 1.08; 95% CI 0.66-1.75; P=0.76; I2 0%) and sotagliflozin (0.16% vs 0.10%; RR 1.09; 95% CI 0.13-8.86; P=0.93; I2 0%). Conclusions: SGLT2i use is associated with a 19.33% lower SAEs of AF/AFL compared with the placebo. Dapagliflozin users had the lowest SAEs of AF/AFL incidence. Further studies are needed to determine whether canagliflozin, empagliflozin, ertugliflozin and sotagliflozin similarly exert protective effects against AF/AFL development.